(3abg GdMjGA (B/s - (3GdebOe, eMeO Hf ESeGYjds 1952- ((3GdEScfOQjI (B:s (3GdOGQ GdYGdejI ddfTQ hGdJhRjY ,s, 2006)
(3jCNPfG GdTjN eMeO Hf ESeGYjd GdebOe aj QMdI Yf GdMjGA hJYQja GdMjGA dZI hTQYG hcja Cf GdMjGA LRA cHjQ ef ecGQe GdCNdGb, hcja Cf GdEfSGf jhdO Ydi GdMjGA hCjVG jecfg GcJSGH GdMjGA hCf GdMjGA fhYGf MjGA aWQj hMjGA cSHj, cPdc jhVM GdcGJH cja jbSe GdMjGA Edi YTQI ChLg, CjVG jJMOK GdcGJH cja Cf ef UaGJ Gddg (B-(3YR hLd(B-(3UaI GdMjGA hCf GdMjGA ef GdEjeGf hcja Cfg jLH Ydi GdEfSGf Cfg dG jSJMj ef Gddg abW Hd jSJMj ef GdfGS hef GdedGFcI hef faSg, bOe GdTjN GdebOe cd gPG hCcKQ GSJTgGOG HBjGJ ef GdbQBf, hcPdc GdcKjQ ef GdCMGOjK, hCHjGJ GdTYQ, hCjVG bUU Yf GdSda GdUGdM, hGdUMGHI hGdUMGHjGJ, hCegGJ GdeDefjf hGdfHj(B-(3Udi Gddg Ydjg hSde(B-.s
Keywords: (3GdCNdGb GdESdGejIs; (3GdMjGAs